DIGITAL ETHICS:: FEATURES AND PROBLEMS OF COMMUNICATION IN ONLINE SALES - V. Moroz, Victoriya; V. Markelova, Yulia; R. Kharisova, Regina; B. Lisitsyna, Tatiana; G. Kartushina, Irina; S. Minkova, Ekaterina; I. Prokopyev, Alexey (Revista Gênero e Interdisciplinaridade, 2021)
The article relevance. New technical capabilities related to the Internet are actively used in all spheres of public life, radically changing the communication models in each of them, including in the business sphere. Digital ethics is one of the areas that is undergoing drastic changes due to the new media environment. The purpose of the study is to determine the role of online communication in online sales. Research methods: as a research method, the survey method was used to identify the features of communication practices in online sales. Research results: the article examines the characteristic features of online sales. The specifics of digital ethics in communications between the manufacturer and the consumer are investigated: the range of technical possibilities for dialogue is determined, the logic of organizing discussion fields is revealed, as well as the degree of their development. The novelty and originality of the research lies in the fact that the digital ethics of social networks for business is being investigated for the first time. It is shown that in large companies, the social network performs a connecting function only at the first stage of cooperation; small businesses practice maintaining long-term contact and the social network function is communicative for them. It is revealed that the social network page serves as a means of informing customers about services and products; for placing ads about promotions and events held in the company; for messages of common nature. It is revealed that social network marketing is not yet fully integrated into the Russian market. It is shown that the format of communication in the social network as a mechanism for accepting applications is characterized by a minimal degree of personification. It is revealed that the dialog space is segmented into an official unit (informative function) and a consumer forum (emotion exchange function). It is revealed that in large and small companies, the functions of dialogue are radically different: for large companies, dialogue is one of the ways to maintain the image, the ability to create the appearance of openness and readiness for interaction, demonstration of customer orientation), for small companies - the ability to remotely and cost-effectively implement products and services, satisfying the individual preferences of each client. Practical significance: the data Obtained in this work can be used in marketing, advertising, social psychology, as well as for further theoretical development of this issue.